The Effect of Education, Income, and Access to Health Services on the Quality of Life of the Elderly in West Java - Jepri Utomo; Arief Yanto Rukmana; Sulistyo Andarmoyo; Dito Anurogo (West Science Social and Humanities Studies, 2023)
This research explores the dynamic interplay between education, income, access to health services, and the quality of life among the elderly in West Java. Utilizing a sample of 120 individuals, the study employs Structural Equation Modeling (SEM-PLS) to analyze the relationships between these key variables. The results reveal that education emerges as a robust predictor, exerting the strongest positive influence on the quality of life among the elderly. Income and access to health services also significantly contribute to well-being, highlighting the multifaceted nature of factors shaping the aging population's quality of life. The findings provide valuable insights for policymakers, practitioners, and researchers aiming to enhance the overall well-being of the elderly in the region.